Community resilience and cultural sustainability in two Finnish urban neighbourhoods - Luonila, Mervi; Kumpulainen, Kaisu; Leppänen, Aino; Koskinen-Koivisto, Eerika; Ruokolainen, Olli (Frontiers in Political Science, 2023)
This study explores how urban cultural environments, and particularly their cultural provision and forms of participation, can foster cultural sustainability in urban communities, namely neighbourhoods. Conceptually, the article situates cultural sustainability within the concept of community resilience to facilitate an understanding of the everyday lives of residents and concerns residents' expectations of the cultural environment and opportunities for cultural participation in two case neighbourhoods in Jyväskylä Finland. Drawing on the mixed-methods approach of the study our findings show that different cultural activities and communities can be central to promoting sustainable urban development. Community resilience as a sense of belonging like neighbourhood-related identity and also as a sense of ownership of place seems strong in various ways, and relation to the cultural participation can be identified. However, from urban cultural policy perspective, the low-threshold participation and opportunities for grassroots cultural activity seem an underexploited resource in the cities, especially when the concept of sustainability is under consideration. Moreover, the negotiation and communication between community actors and public officials deserves a lot of attention while the implementation of urban cultural policy is on focus. From urban cultural policy perspective, it is important to find new ways to measure the direct and indirect impacts of policies. According to findings of the study holistic analysis of residents, actors and institutions viewpoints helps us to understand the practises and processes related to community resilience. All this deserves multidisciplinary research and joint reflection. This approach assists to make sense of how urban cultural policy and cultural participation can support community resilience at community level.